Characterization of In Vitro Chlamydia muridarum Persistence and Utilization in an In Vivo Mouse Model of Chlamydia Vaccine. (18th February 2013) - Carey, Alison J.; Huston, Wilhelmina M.; Cunningham, Kelly A.; Hafner, Louise M.; Timms, Peter; Beagley, Kenneth W.
<x xml:space="preserve">Abstract</x> Problem Chlamydia trachomatis genital tract infections are easily treated with antibiotics; however, the majority of infections are asymptomatic and therefore untreated, highlighting the need for a vaccine. Because most infections are asymptomatic, vaccination could potentially be administered to individuals who may have an acute infection at that time. In such individuals, the effect of vaccination on the existing infection is unknown; however, one potential outcome could be the development of a persistent infection. In vitro chlamydial persistence has been well characterized in various strains; however, there have been no reported studies in C. muridarum. Method of Study We performed ultrastructural characterization and transcriptome analysis of selected genes. We then used the transcriptional profiles of the selected genes to examine whether intranasal immunization of mice during an active genital infection would induce persistence in the upper reproductive tract of female mice. Results and Conclusions We found that persistence developed in the oviducts of mice as a result of immunization. This is a significant finding, not only because it is the first time that C. muridarum persistence has been characterized in vitro, but also due to the fact that there is a minimal characterization of in vivo persistence of any chlamydial species. This highlights the importance of the timing of vaccination in individuals.